Growth, distribution and poverty in Africa : messages from the 1990s - Christiaensen, Luc J.; Demery, Lionel; Paternostro, Stefano (Washington, D.C. : World Bank, 2002)
Provides details of the results of a series of country studies. These studies have made use of vastly improved household survey data, which have enhanced understanding of African poverty dynamics during the past decade. This book examines the main factors behind observed poverty changes in eight countries--Ethiopia, Ghana, Madagascar, Mauritania, Nigeria, Uganda, Zambia, and Zimbabwe. After reviewing the trends in income poverty and other more direct measures of well-being such as education, health, nutrition, the book goes beyond the aggregate numbers and highlights the insights to be gained from clarifying the microeconomic data. This book calls for public action to ensure that all poor Africans gain from future economic growth.
Includes bibliographical references (p. 65-69).
opc12/1/17
Loans
Keywords: Cost and standard of living; Poverty; Economic policy; Income; Economic history and conditions; Cost and standard of living; Africa